2013
DOI: 10.1021/ja406144h
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Shaped Re(I) Multinuclear Complexes with Unique Photofunctional Properties

Abstract: We synthesized for the first time a series of emissive ring-shaped Re(I) complexes (Re-rings) with various numbers of Re(I) units and various lengths of bridge ligands. The photophysical properties of the Re-rings could be varied widely through changes in the size of the central cavity. A smaller central cavity of the Re-rings induced intramolecular π-π interactions between the ligands and consequently caused a stronger emission and a longer lifetime of the excited state. The Re-rings can function as efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 26 publications
2
93
1
1
Order By: Relevance
“…, the size of the ring and the type of the bridging bisphosphine ligand P–P) and their photophysical and electrochemical properties. 1618 The trinuclear Re-ring connected with a phenylene spacer in the bisphosphine ligand exhibited both a long lifetime and a strong oxidation power in the excited state. The corresponding OERS, which are important intermediates in the redox-photosensitized reactions, were relatively stable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, the size of the ring and the type of the bridging bisphosphine ligand P–P) and their photophysical and electrochemical properties. 1618 The trinuclear Re-ring connected with a phenylene spacer in the bisphosphine ligand exhibited both a long lifetime and a strong oxidation power in the excited state. The corresponding OERS, which are important intermediates in the redox-photosensitized reactions, were relatively stable.…”
Section: Resultsmentioning
confidence: 99%
“…1618 They exhibited outstanding photophysical and electrochemical properties, such as high emission quantum yields, along with long lifetimes of the 3 MLCT excited states, even in solution at room temperature, and stability in the excited state and stronger oxidation power in the excited state compared to the corresponding mononuclear Re complex. They can also photochemically accumulate multiple electrons in one molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, the thermal instability of metal complexes or the photobleaching of photosensitizers limits their practical application. Recently, Ishitani and co‐workers demonstrated that the photophysical properties of Re complexes can be widely tailored in a series of emissive ring‐shaped Re complexes . The Re rings work as an efficient photosensitizer and widely utilize visible light for CO 2 reduction with quantum yields of up to 82 % in the presence of Re−MeCN + .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Very recently, we also developed ring-shaped multinuclear Re(I) complexes that comprise a linkage of Re I (N^N)(CO) 2 units with bidentate phosphine-alkyl ligands PPh 2 −(CH 2 ) m − PPh 2 (m = 2−6) (P−P) (the structures of some examples are shown in Chart 1 as Rne and Rnb for m = 2 or 4, respectively). 20,21 Interestingly, some of these Re-rings exhibited outstanding photophysical and electrochemical properties and were more suitable as a redox photosensitizer, even compared with the corresponding linear multinuclear complexes and the mononuclear complexes cis,trans-[Re-(N^N)(CO) 2 {PPh 2 (C n H 2n+1 )} 2 ] + . These Re-rings exhibited longer lifetimes and greater oxidation power of the 3 MLCT excited state as well as photochemical multielectron accumulation in a single molecule.…”
Section: ■ Introductionmentioning
confidence: 99%